Significance of the middle Cambrian (Wuliuan) trilobite Pagetia from Yorke Peninsula, South Australia. Issue 7 (2nd October 2020) - Jago, J. B.; Kruse, P. D.
Abstract: The presence of a trilobite, assigned to Pagetia cf. edura, from the Coobowie Limestone in the Port Julia-1A drillhole on Yorke Peninsula indicates that sedimentation in the Stansbury Basin, and probably also in the Arrowie Basin, did not terminate until at least the Wuliuan (middle Cambrian, Templetonian). It further indicates that the folding of the Delamerian Orogeny did not commence until at least the Wuliuan (509–504.5 Ma).